The Application of Qur'anic Values Regarding Visual Impairment at Yaketunis in Yogyakarta - Arif Friyadi; Ahmad Saerozi; Umma Farida; Abdul Karim (Universitas Muhammadiyah Surakarta, 2026)
Purpose - This study examines how Qur'anic values are implemented in the education and empowerment of visually impaired individuals at the Islamic Welfare Foundation for the Visually Impaired (Yayasan Kesejahteraan Tunanetra Islam - Yaketunis) in Yogyakarta. The research seeks to explore how Islamic principles of equality, dignity, compassion, and human empowerment are translated into educational practices for persons with visual impairments.Design/methodology/approach - The study employs a descriptive qualitative approach. Data were collected through observations, in-depth interviews, and documentation involving teachers, students, and institutional administrators. The data were analyzed thematically to identify patterns in the implementation of Qur'anic values within educational activities and dormitory life. Findings - The findings reveal that Yaketunis has successfully integrated key Qur'anic values into its educational system and daily practices. The value of tawḥīd is manifested through worship activities and spiritual development programs. Equality is reflected in inclusive educational practices and recognition of individual potential regardless of physical limitations. Compassion is demonstrated through humanistic social interactions and mutual support among members of the institution. Meanwhile, independence is fostered through life-skills education, vocational training, and self-development programs. These values collectively contribute to the personal, social, and spiritual empowerment of visually impaired individuals. Research implications/limitations - The study is limited to a single Islamic educational institution and focuses primarily on visually impaired learners. Future research may compare similar institutions or examine the implementation of Qur'anic values among other groups with disabilities. Originality/value - This study contributes to the discourse on Islamic inclusive education by demonstrating how Qur'anic values can serve as a practical framework for empowering persons with disabilities. It positions Yaketunis as a model of humanistic and transformative Islamic education that promotes dignity, inclusion, and self-reliance.